L’EDIZIONE CARDANIANA DEL CONSIGLIO NAZIONALE DELLE RICERCHE; UN’OCCASIONE PERDUTA (Istituto Lombardo - Accademia di Scienze e Lettere - Rendiconti di Scienze, 2014)
The Cardano edition from the Consiglio nazionale delle ricerche has been a wasted opportunity. It shows the lack of an accurate systematic approach that led to the Cardano Project ending in failure. The project had been fostered by the “National research council Center for the study of philosophical thought in the 16th and 17th centuries in relation to scientific questions”, set up by Mario Dal Pra. The aim had been for it to prepare a critical edition of the works of the doctor, mathematician, astrologist and philosopher Girolamo Cardano (Pavia 1501-Rome 1576).